Pure Headwaters in the Flint Hills - Walter Dodds (Symphony in the Flint Hills, 2013)
The most inviting and pleasant place on the prairie landscape is the stream. In the biting winter winds, the bison hunker down for shelter and if it is too hot, the cattle seek its coolness. Water is lifeblood.
Keywords: nature; natural; native; bird; animal; winter; water; headwater; flint hills; migration; bison; buffalo; historical; ancient; Native American; Osage River; Arkansas River; Kansas River; blue heron; cattle; summer; ecosystem; biotic; fish; Topeka Shiner; orange-throat darter; lakes; bonds; wetlands; ice sheet; glacier; grassland; prairie; plains; tallgrass; streams; pools; Unionid mussels; endangered species; midwest; algae